Assessment of the Nutritional Status of first year primary school children in El Horga village, Gezira state - Abdalla, Zeinab El Samani; Babikir, Hayder El Hadi; Ali, Khalid El Tom (مجلة الجزيرة للعلوم الصحية; مجلد 1 عدد 1 (2003), 2003)
Objective: To assess the nutritional status of first year primary school children in El Horga village as a basis for further intervention. Methods: A cross-sectional study was conducted in all first year primary school children, aged 6-7 years, in El Horga village, in the Gezira State, central Sudan, 53 males and 62 females. The study was designed to assess the nutritional status using clinical signs, standard anthropometric measurements and biochemical investigations. Results: Mean anthropometric measurements were 19.1± 2.6 kg for weight, and 112.5±5.1 cm for height. Compared to National Center for Health Statistics (NCHS) reference parameters, 63.5% of children were stunted (height for age, H/A <-2 Z score), 18.3% were wasted (weight for height, W/H <-2 Z score) and 57.5% underweight (weight for age, W/A< -2 Z score). Mean for mid upper circumference (MUAC) was 16.7± 0.2 cm, and 8.4± 0.19 mm for triceps skin fold (TSF). According to MAUC, 45.2% of children suffered malnutrition, 28.7% were moderately undernourished and 16.5% were severely undernourished. Significantly low adipose tissue stores were found in 41.8%.  Biochemical results were as follows: mean haemoglobin (Hb) concentration of all children was 11.4±1.2 g/dl, PCV 34.1±2.2%, MCHC 32.8±2.4g/dl. total serum protein 6.8±0.9 g/dl, serum albumin 4.0±0.8 g/dl, serum iron 50.2±21.2µg/dl, TIBC 266.6±51.6µg/dl, and 21.2±8.6% transferrin saturation. 56.5% of the study group were anaemic (Hb<11g/dl) and 30.4% suffered from iron deficiency anaemia with transferrin saturation <15%.